Cardiovascular involvement among collegiate athletes following COVID-19 infection - Guevarra, C. C.; Murray, N.; Cipriani, D.; Mailland, K.; Char, A.; Coffman, K.; Davis, C.; Truong, F.; Danielian, A.; Barnes, G.; Gaal, W. (Journal of Clinical and Translational Research, 2022)
Background: Recent studies suggest that the prevalence of cardiac involvement in young competitive athletes with SARS-CoV-2 infection appears to be low. Aim: This study aimed to determine the prevalence of cardiovascular involvement in young competitive athletes. Methods: In this single-center retrospective cohort study from one Division I university, we assessed the prevalence of cardiovascular involvement among collegiate athletes who tested positive for SARS-CoV-2 by polymerase chain reaction (PCR) testing. Data were collected from June 25, 2020, to May 15, 2021. The primary outcome was the prevalence of cardiac involvement based on a comparison of pre-and post-infection ECGs. The secondary outcome was to evaluate for any association between ethnicity and the presence or absence of symptoms. Results: Among 99 athletes who tested positive for the SARS-CoV-2 virus (mean age 19.9 years [SD 1.7 years]; 31% female), baseline ECG changes suggestive of cardiovascular involvement post-infection were detected in two athletes (2/99; 2%). There was a statistically significant association between ethnicity and the presence or absence of symptoms, Chi²(3, N = 99) = 10.61, p = 0.01. Conclusions. The prevalence of cardiovascular involvement amongst collegiate athletes following SARS-CoV-2 infection in this cohort is low. Afro-American and Caucasian athletes are more likely to experience symptoms following SARS-CoV-2 infection in comparison to Hispanic and Pacific Islander athletes, however, there is no association between ethnicity and symptom severity. Relevance for patients: These data add to the growing body of literature and agree with larger cohorts that the risk of cardiac involvement post-infection appears to be low among elite athletic and semi-professional athletic populations.